Types of Code-Switching Take from Tasya Kamila Instagram Account - I Dewa Ayu Devi Maharani Santika; Ni Luh Putu Januartini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Nowadays, code-switching has been widely used by the public in communicating on social media or directly. This study aims to analyze the types of code-switching from Indonesian to English and vice versa on Tasya Kamila Instagram Account. The descriptive qualitative method is used for this study to analyze the data. The data were analyzed using the theory from Poplack (1980). There are 3 types of code-switching based on theory from Poplack (1980) such as tag-switching, inter-sentential switching, and intra-sentential switching. The types of code-switching that use 5 data of tag-switching with percentage (8.62%), 28 data of intersentential switching with percentage (48,28%), and 25 data of intra-sentential switching with percentage (43,10%). Based on the results of research, Tasya Kamila is dominantly using intersentential switching in writing captions for each photo or video on her Instagram account.